SOME ISSUES RELATED TO PROBATION CONTRACT UNDER LABOR CODE 2012 - Nguyễn Văn Tố Hữu (Tạp chí Khoa học Đại học Đà Lạt)
The purpose of strict regulations on probation contracts is to safeguard the rights and legitimate interests of employees and employers in the probation period. The 2012 Labor Code and other related documents extensively update many regulations on probation contracts, but such regulations still retain certain limitations. This paper presents a general overview, describes improvements, and analyses the limitations of current regulations in regard to probation contracts.